Evaluasi Kepuasan Pengguna Aplikasi Inspekta di PT. PLN UP2D S2JB Menggunakan Metode Pieces - Aditya Revaldo; Imamulhakim Syahid Putra (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to evaluate user satisfaction with the Inspekta Application at PT PLN UP2D S2JB using the PIECES Framework approach, which covers six key aspects: Performance, Information, Economy, Control, Efficiency, and Service. Data was collected through questionnaires distributed to 30 respondents who are active users of the application. The analysis results show that all PIECES indicators scored in the "satisfied" category, with the highest score in the efficiency aspect (4.14) and the lowest in the economic aspect (3.80). Although the Inspekta application has generally had a positive impact on operational efficiency and reporting processes, improvements are still needed in data security and technical support. This study offers strategic recommendations to enhance application quality and support the organization’s overall performance.